Adolescent religious attendance and spirituality-Are they associated with leisure-time choices? - Klara Malinakova; Andrea Madarasova Geckova; Jitse P van Dijk; Michal Kalman; Peter Tavel; Sijmen A Reijneveld (PLoS ONE)
Background Spirituality and religious attendance (RA) have been associated with personal attitudes and values, and this may affect lifestyle. The aim of this study was to explore their association with adolescent leisure-time choices in a highly secular environment. Methods A nationally representative sample of adolescents (n = 4,182, 14.4±1.1 years, 48.6% boys) participated in the 2014 Health Behaviour in School-aged Children cross-sectional study. We measured RA, spirituality (adjusted shortened version of the Spiritual Well-Being Scale), excessive television, computer games, and internet use, as well as participation in organized leisure-time activities. Results Compared to non-attending and non-spiritual respondents, respectively, both attending respondents and spiritual respondents were less likely to watch television and play computer games excessively, with odds ratios (ORs) ranging from 0.6 (95% confidence interval 0.5-0.8) to 0.92 (0.9-0.99). Only attending and only spiritual respondents were more likely to use the internet excessively, but this was not the case for those that were both attending and spiritual. Moreover, religious and spiritual respondents were more likely to be involved in at least one organised activity. ORs were 2.9 (1.9-4.3) for RA and 1.3 (1.2-1.4) for spirituality compared to their counterparts. The same pattern was observed for sporting and non-sporting activities combined (ORs 4.6 (3.0-7.1) and 1.5 (1.4-1.7), respectively) and regularly reading books or playing a musical instrument. Conclusions Adolescent RA and spirituality are associated with a more active way of spending leisure-time. Further research should focus on understanding potential mechanisms that underlie these associations.